Evaluation of the Medical Assistance to Patients with Arterial Hypertension in Four Urban Áreas - Addys Díaz Piñera; Armando Rodríguez Salvá; Susana Balcindes Acosta; René García Roche; Nelsy Álvarez Mesa (Revista Finlay, 2018)
Foundation: improving the quality of assistance is a challenge for all in charge of providing health services. It is no enough to know what happens but also to modify unsatisfactory results. Objective: to evaluate the quality of the medical assistance which patients with hypertension receive by means of the program observance in four health areas during 2013. Methods: a research of the health systems and services was done, using a two stage conglomerate sample. The variables studied were related to the coverage and quality of human resources, the availability of material resources, the compliance of the main activities set for the process of assistance. Various instruments approved by experts were applied to hypertensive population. More than 85 % of clinical records were audited. For collecting and analyzing data statistic packages Access 2000 and SPSS 15, 0 were used. Results: the evaluation of structure, process and results dimensions was not satisfactory in the studies area, because the proposed standards were not achieved. Conclusion: the assistance received by these patients is not appropriate since there were difficulties in the program compliance, which influenced in the quality provided.